A Cross Sectional Study on Awareness of Sex Determination Techniques & Gender Preference Among Married Women in An Urban Slum of Maharashtra - Bedre, Rahul; Solanki, Harsha (National Journal of Community Medicine, 2014)
Background: Skewed sex ratio is an issue of major concern & has long term Sociodemograhic consequences which may be due to patriarchal social framework & strong son desire in India. The problem is getting worse as scientific methods of sex determination & termination of pregnancy are improving leading to female feticide. Hence the present study tries to evaluate knowledge & practice of sex-determination techniques & reasons for son preference gender among married women in an urban slum of Mumbai, Maharashtra. Methodology: A community based, cross-sectional study was carried out among 900 married women of reproductive age group selected by systematic random sampling in an urban slum of community of Mumbai, Maharashtra. Results: the present study shows that most of the women were muslims & they were educated. In spite of good education most of the women were engaged in household work. Most of the women i.e. 58.8% were aware of sex determination practices of which majority knew the method & place of sex determination as well as majority knew that sex determination is crime & few women were aware about the penalty for the same. Overall male child preference was seen in 49.6% women. The desire for male child becomes stronger as the number of girl child increases. Major reasons for male child preference were to carry forward family name & business, for their old age support & to carry out religious function. Conclusion: The present study reflects that knowledge of sex determination techniques were quite good among study women as well as they were having strong preference for male child.